PERENCANAAN REKRUTMEN TENAGA KEPENDIDIKAN DI MADRASAH ALIYAH DARUSSALAM BUMI AGUNG - Ibrahim, Ibrahim; Niswah, Choirun; Wulandari, Yunita (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract: This research is entitled "Planning the Recruitment of Education Personnel at Madrasah Aliyah Arussalam Bumi Agung Oki". This study aims to find out how the recruitment of educational staff and the factors that influence the planning of educational staff recruitment at Madrasah Aliyah Darussalam Bumi Agung Oki. The type of research used in this research is qualitative research. Data collected through observation, interviews and documentation. This type of research approach is descriptive qualitative. The techniques used in data analysis are data reduction, data presentation and drawing conclusions. Test the validity of the research data using technical triangulation and source triangulation. The results of this study indicate that planning for the recruitment of educational staff at Madrasah Aliyah Darussalam Bumi Agung Oki is starting from setting targets or goals, formulating the current situation, identifying all facilities and obstacles, and developing plans or a series of activities to achieve goals. The factors that influence recruitment activities are facilities, teamwork, economic factors and labor supply. Keywords: Planning, Recruitment, Education Personnel